Effectiveness of exercise interventions on mental health and health-related quality of life in women with polycystic ovary syndrome: a systematic review - Rhiannon K. Patten; Michaela C. Pascoe; Alba Moreno-Asso; Russell A. Boyle; Nigel K. Stepto; Alexandra G. Parker (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex condition, impacting cardio-metabolic and reproductive health, mental health and health-related quality of life. The physical health benefits of exercise for women with PCOS are well-established and exercise is increasingly being recognised as efficacious for improving psychological wellbeing. The aim of this review was to summarise the evidence regarding the effectiveness of exercise interventions on mental health outcomes in women with PCOS. Methods A systematic search of electronic databases was conducted in March of 2020. Trials that evaluated the effect of an exercise intervention on mental health or health-related quality of life outcomes in reproductive aged women with diagnosed PCOS were included. Methodological quality was assessed using the modified Downs and Black checklist. Primary outcomes included symptoms of depression and anxiety, and health-related quality of life. Results Fifteen articles from 11 trials were identified and deemed eligible for inclusion. Exercise demonstrated positive improvements in health-related quality of life in all of the included studies. Half of included studies also reported significant improvements in depression and anxiety symptoms. There was large variation in methodological quality of included studies and in the interventions utilised. Conclusions The available evidence indicates that exercise is effective for improving health-related quality of life and PCOS symptom distress. Exercise also shows some efficacy for improving symptoms and/or prevalence of depression and anxiety in women with PCOS. However, due to large heterogeneity of included studies, conclusions could not be made regarding the impact of exercise intervention characteristics. High-quality trials with well reported exercise intervention characteristics and outcomes are required in order to determine effective exercise protocols for women with PCOS and facilitate translation into practice.